Ka-Band metalens antenna empowered by physics-assisted particle swarm optimization (PA-PSO) algorithm - Jiang, Shibin; Deng, Wenjun; Wang, Zhanshan; Cheng, Xinbin; Tsai, Din Ping; Shi, Yuzhi; Zhu, Weiming (Opto-Electronic Science, 2024)
Design of multiple-feed lens antennas requires multivariate and multi-objective optimization processes,which can be ac-celerated by PSO algorithms.However,the PSO algorithm often fails to achieve optimal results with limited computation resources since spaces of candidate solutions are quite large for lens antenna designs.This paper presents a design paradigm for multiple-feed lens antennas based on a physics-assisted particle swarm optimization(PA-PSO)algorithm,which guides the swarm of particles based on laws of physics.As a proof of concept,a design of compact metalens an-tenna is proposed,which measures unprecedented performances,such as a field of view at±55°,a 21.7 dBi gain with a flatness within 4 dB,a 3-dB bandwidth>12°,and a compact design with a f-number of 0.2.The proposed PA-PSO algo-rithm reaches the optimal results 6 times faster than the ordinary PSO algorithm,which endows promising applications in the multivariate and multi-objective optimization processes,including but not limited to metalens antenna designs.